If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 + -1(4x + 4) = 4(x + 6) + x Reorder the terms: 64 + -1(4 + 4x) = 4(x + 6) + x 64 + (4 * -1 + 4x * -1) = 4(x + 6) + x 64 + (-4 + -4x) = 4(x + 6) + x Combine like terms: 64 + -4 = 60 60 + -4x = 4(x + 6) + x Reorder the terms: 60 + -4x = 4(6 + x) + x 60 + -4x = (6 * 4 + x * 4) + x 60 + -4x = (24 + 4x) + x Combine like terms: 4x + x = 5x 60 + -4x = 24 + 5x Solving 60 + -4x = 24 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 60 + -4x + -5x = 24 + 5x + -5x Combine like terms: -4x + -5x = -9x 60 + -9x = 24 + 5x + -5x Combine like terms: 5x + -5x = 0 60 + -9x = 24 + 0 60 + -9x = 24 Add '-60' to each side of the equation. 60 + -60 + -9x = 24 + -60 Combine like terms: 60 + -60 = 0 0 + -9x = 24 + -60 -9x = 24 + -60 Combine like terms: 24 + -60 = -36 -9x = -36 Divide each side by '-9'. x = 4 Simplifying x = 4
| 3x+1/2*3=0 | | 5x+20y=28c | | (w-1)(w-1)= | | 1/2ms | | X-x^2=42 | | 16-1/3x=11 | | 2/5sm | | 13x^2-840x-5040=0 | | 3(w-6)-5w= | | R(1-DT)=D | | -5x+8=3-4x | | 2/3x-84 | | 17-1/3x=11 | | x(x+6)=(x+3)2 | | 56t+62t=42 | | 6(x+3)+2=-16 | | 25x-8-16x+3=25x-4-16x+13 | | %nbsp;= eg;[3] | | -6-y=13 | | x^2+2.4x+1.44=0 | | 22=-7v+5(v+6) | | f(x)=x^2+3(4x)+17 | | (5x+3)(6x^2+8x+9)=0 | | f(x)=1000(.04-x^2) | | -x+12=17 | | 12k-[4k+(-4+2k)]=0 | | x^4+x^3+30x^2-44x=22 | | 7(x+2)+9=-19 | | 100+2x+y+5x+y=180 | | 3=y/8-10 | | 8.00(x+4.00)=72 | | 5x-6+19x=22 |